2015
DOI: 10.3390/molecules20058048
|View full text |Cite
|
Sign up to set email alerts
|

Composition of the Essential Oil of Salvia ballotiflora (Lamiaceae) and Its Insecticidal Activity

Abstract: Essential oils can be used as an alternative to using synthetic insecticides for pest management. Therefore, the insectistatic and insecticidal activities of the essential oil of aerial parts of Salvia ballotiflora (Lamiaceae) were tested against the fall armyworm Spodoptera frugiperda (Lepidoptera: Noctuidae). The results demonstrated insecticidal and insectistatical activities against this insect pest with concentrations at 80 µg·mL . This oil also increased the duration of the larval phase by 5.5 days and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 21 publications
2
22
0
1
Order By: Relevance
“…Subsequent studies by Cárdenas-Ortega et al 20 reported 37 different compounds with β-caryophyllene and caryophyllene oxide as main components in Salvia ballotiflora resulted in 80% larval mortality. Evans 56 reported that alkaloids cause the death of treated organisms due to their ability to bind DNA of organisms and affecting the replication process and synthesis of molecules.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Subsequent studies by Cárdenas-Ortega et al 20 reported 37 different compounds with β-caryophyllene and caryophyllene oxide as main components in Salvia ballotiflora resulted in 80% larval mortality. Evans 56 reported that alkaloids cause the death of treated organisms due to their ability to bind DNA of organisms and affecting the replication process and synthesis of molecules.…”
Section: Discussionmentioning
confidence: 98%
“…Twenty larvae of Cx. quinquefasciatus were treated with different concentrations of each extract individually and in combination with microbes (1:1 volume); P. aeruginosa and Bacillus thuringiensis israelensis (Bti) along with control group and group treated with different concentrations of permethrin (10,20,30,50, 100, 150 and 250 ppm) in water. Three replicates were performed for each test and the mortality data was recorded at 24, 48 and 72 hours of post treatment 16 .…”
mentioning
confidence: 99%
“…In our study, S.officinalis mainly consisted of 1,8 cineole, caryophyllene, camphor, α-pinene and borneol. However, the major component of essential oils of some Salvia genus were beta-caryophyllene and caryophyllene oxide for S. hydrangea and S. ballotiflora (Sonboli et al, 2006;Cardenas-Ortega et al, 2015); aromadendrene oxide-(1), cadinol and germacrene D for S. miltiorrhiza; Limonene, terpineol and eudesmol for S. przewalskii and thujene for S.officinalis (Li et al, 2015). Vitis species have active components for human diet because of their nutritional value and vital compounds to be protected from disease.…”
Section: Discussionmentioning
confidence: 99%
“…Bioactivity studies of the chemical constituents found in COR and other botanical species revealed that they have different modes of action for insects (feeding inhibition and toxic activity repellency either by contact or by fumigation) (GERIS et al, 2008;ALVES et al, 2012;CHAUBEY, 2012;CÁRDENAS-ORTEGA et al, 2015;SANTOS et al, 2016). Recently, it was found that methanolic extracts of leaves and dried shells of Copaifera langsdorffi Desf.…”
Section: O R + T R I a Z O P H O S C O R + C H L O R P Y R I F O S mentioning
confidence: 99%
“…This is basically composed of sesquiterpene oxygenated hydrocarbons, predominantly β-caryophyllene, β-bisabolene, β-bergamoteno and β-selinene (VEIGA JUNIOR; PINTO, 2002). Recently, Cárdenas-Ortega et al (2015) found that the essential oil from Salvia ballotiflora Benth (Lamiaceae), which also contains β-caryophyllene (12.74%) among its major components, showed insecticidal activity in S. frugiperda, leading to a decrease in the viability of caterpillars and pupae. However, copaiba oil-resin (COR) has been shown to be toxic to Sitophilus zeamais Motschulsky (Coleoptera: Curculionidae) .…”
Section: Introductionmentioning
confidence: 99%